SOCIAL TRANSFORMATIONS AND MORAL CHANGE IN POST-SOVIET SOCIETIES: WELFARE INSTITUTIONS, FAMILY, AND EDUCATION IN THE TRANSITION FROM PLANNED TO MARKET ECONOMY - Himmlegaard, Michael (Farabi Journal of Social Sciences, 2026)
Purpose. This paper investigates how the transition from planned to market economies in post-Soviet societies has reshaped moral orders, trust relations, and institutional legitimacy across welfare, family and education systems. By applying a philosophical sociology of knowledge, the study conceptualizes moral change not as a decline of values, but as a reorganization of collective meaning. Design/methodology/approach. The study employs a comparative and interpretive qualitative research design. It integrates classical theoretical frameworks (Durkheim, Mannheim, Bourdieu, Collins) with recent empirical research (2015–2025) across six post-Soviet societies: Russia, Ukraine, Kazakhstan, Uzbekistan, Lithuania and Poland. The analysis draws on academic literature, survey data and institutional discourse. Findings. Findings show that welfare, family and education systems have undergone moral hybridization, combining residual collectivist norms with emergent neoliberal ethics. Welfare shifted from solidarity to conditionality; families became the primary moral and economic safety net; and education adopted meritocratic individualism. These changes have fragmented social trust and legitimacy, while also generating new forms of agency, civic mobilization and moral innovation. Originality/value. Instead of interpreting post-Soviet transformation as moral loss, the paper demonstrates that moral change is a relational process embedded in institutional restructuring, emotional dynamics and epistemic transition. The study advances philosophical sociology as a theoretical lens for understanding how societies reorder moral meaning under systemic change. Keywords: Moral change; Post-Soviet societies; Social transformation; Welfare; Family; Education; Philosophical sociology; Social trust